Lost in Transition: Health Care Experiences of Adults Born Very Preterm—A Qualitative Approach - Perez, Anna; Thiede, Luise; Lüdecke, Daniel; Ebenebe, Chinedu Ulrich; von dem Knesebeck, Olaf; Singer, Dominique (Frontiers in Public Health, 2020)
Introduction: Adults Born Very Preterm (ABP) are an underperceived but steadily increasing patient population. It has been shown that they face multiple physical, mental and emotional health problems as they age. Very little is known about their specific health care needs beyond childhood and adolescence. This article focuses on their personal perspectives: it explores how they feel embedded in established health care structures and points to health care-related barriers they face. Methods: We conducted 20 individual in-depth interviews with adults born preterm aged 20 to 54 years with a gestational age (GA) below 33 weeks and birth weights ranging from 870 g to 1950 g. Qualitative content analysis of the narrative interview data was conducted to identify themes related to self-perceived health, health care satisfaction and social well-being. Results: The majority (85%) of the study participants reported that their former prematurity is still of concern in their everyday lives as adults. The prevalence of self-reported physical (65%) and mental (45%) long-term sequelae of prematurity was high. Most participants expressed dissatisfaction with health care services regarding their former prematurity. Lack of consideration for their prematurity status by adult health care providers and the invisibility of the often subtle impairments they face were named as main barriers to receiving adequate health care. Age and burden of disease were important factors influencing participants’ perception of their own health and their health care satisfaction. All participants expressed great interest in the provision of specialized, custom-tailored health-care services, taking the individual history of prematurity into account. Discussion: Adults born preterm are a patient population underperceived by the health care system. Longterm effects of very preterm birth, affecting various domains of life, may become a substantial burden of disease for subgroups of formerly preterm individuals and should therefore be taken into consideration by adult health care providers.